Biochemical response between insects and plants: an investigation of enzyme activity in the digestive system of Leucoptera coffeella (Lepidoptera: Lyonetiidae) and leaves of Coffea arabica (Rubiaceae) after herbivory. (19th February 2018) - Meriño‐Cabrera, Y.; Zanuncio, J.C.; da Silva, R.S.; Solis‐Vargas, M.; Cordeiro, G.; Rainha, F.R.; Campos, W.G.; Picanço, M.C.; de Almeida Oliveira, M.G.
Abstract: Plant defence mechanisms can reduce the digestive enzyme activity of insect pests. The aim of this study was to determine the relationship between the production of proteinase inhibitors, lipoxygenase and polyphenol oxidase activity in Coffea arabica (Catuai IAC 15) plants, and the digestive enzyme activity in the pest Leucoptera coffeella ( Lepidoptera : Lyonetiidae ) after feeding on the plant. The production of proteinase inhibitors was evaluated with L‐BApNA as a substrate. We studied lipoxygenase activity with linoleic acid and polyphenol oxidase activity with catechol substrates, in coffee plants damaged (T1) and not damaged (T2) by L. coffeella . L. coffeella digestive enzyme activity was verified by trypsin ‐ like (substratel ‐BApNA andl ‐TAME), chymotrypsin ‐ like (BTpNA and ATEE), cysteine proteases (l ‐BApNA) and total protease (azocasein). Proteinase inhibitor production and lipoxygenase and polyphenol oxidase activity in C. arabica increases ( P ≤ 0.05) with L. coffeella damage. Our results provide important information that these enzymatic activities may play a role in plant defence processes in C. arabica . Trypsin ‐ like activity increases, whereas chymotrypsin‐like and cysteine protease activity decrease in the midgut of L. coffeella, which acts as a defence mechanism. Abstract : Protease inhibitor production, PPO and LOX activity in C. arabica plants, have no effect on reducing the proteolytic activity in L. coffeella . An increase in essential protease trypsin‐like activity and a decrease of secondary ones such as chymotrypsin‐like activity was founded in the digestive system of L. coffeella, in response to these plant defence mechanisms.